2010
DOI: 10.1016/j.brainres.2009.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in familiarity and recollection across the lifespan: An ERP perspective

Abstract: The ability to recognize previous experience depends on two neurocognitive processes, familiarity, fast-acting and relatively automatic, and recollection, slower-acting and more effortful. Familiarity appears to mature relatively early in development and is maintained with aging, whereas recollection shows protracted development and deteriorates with aging. To assess this model, ERP and behavioral data were recorded in children (9-10 years), adolescents (13-14), young (20-30) and older (65-85) adults during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
65
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 75 publications
6
65
1
Order By: Relevance
“…Research dissecting the heterogeneity of older adults according to high and low cognitive performance has been valuable for examining associated neural mechanisms underlying variation in function (Daselaar, Veltman, Rombouts, Raaijmakers, & Jonker, 2003;De Sanctis, Gomez-Ramirez, Sehatpour, Wylie, & Foxe, 2009;Friedman, de Chastelaine, Nessler, & Malcolm, 2010;Wiegand et al, 2014;Wolk et al, 2009). Nevertheless, differentiating individual differences in performance, based on the same dependent variable that is used to measure this performance, increases the statistical risk of regression towards the mean when attempting to divide subtypes of elderly.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Research dissecting the heterogeneity of older adults according to high and low cognitive performance has been valuable for examining associated neural mechanisms underlying variation in function (Daselaar, Veltman, Rombouts, Raaijmakers, & Jonker, 2003;De Sanctis, Gomez-Ramirez, Sehatpour, Wylie, & Foxe, 2009;Friedman, de Chastelaine, Nessler, & Malcolm, 2010;Wiegand et al, 2014;Wolk et al, 2009). Nevertheless, differentiating individual differences in performance, based on the same dependent variable that is used to measure this performance, increases the statistical risk of regression towards the mean when attempting to divide subtypes of elderly.…”
Section: Introductionmentioning
confidence: 97%
“…Such effects are consistent with dual-process models of recognition (Mandler, 1980;Yonelinas, 2002) that dissociate the feeling that an item has been experienced before (familiarity) from a detailed explicit memory of the event (recollection). Research has explored individual differences by categorising elderly samples into high and low performers (Friedman et al, 2010;Wolk et al, 2009) and have found preservation in recollection-based processing associated with parietal effects in the high performers and young but the absence of this parietal modulation in older low performers.…”
Section: Introductionmentioning
confidence: 98%
“…Developmental findings from animal models (13) and initial evidence from human studies (14) suggest that the DG matures later than other HC subfields. Likewise, memory functions associated with pattern separation, such as recollection (6), show a protracted course of development that extends well into middle childhood (15). Thus, the DG is a candidate region of interest (ROI) for investigating developmental associations between HC and pattern separation.…”
mentioning
confidence: 99%
“…The relationship between recollective experience and FOK accuracy is especially important regarding aging, where both subjective measures (e.g. Remember/Know: Bugaiska et al, 2007;Friedman et al, 2010) and objective measures (e.g. source memory tasks: Henkel et al, 1998;Thomas et al, 2011) indicate a recollective deficit in older adults.…”
Section: Introductionmentioning
confidence: 99%